EFFECT OF FEEDING BYPASS PROTEIN ON BLOOD BIOCHEMICAL PROFILE OF BARBARI KIDS - Singh, VP; Nayak, S; Baghel, RPS; Patile, AK; Khare, AK (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The objective of this study was to evaluate the effect of protected ground nut cake (GNC) on blood biochemical profile of growing goats. Results of study indicated that blood biochemical parameters comprising total protein, albumin and globulin were significantly (P<0.05) higher in kids fed on formaldehyde treated GNC based ration, but average blood urea nitrogen concentration significantly (P<0.01) decreased in kids fed on formaldehyde treated GNC based ration.